(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
What is the current interpretation of early childhood learning? How do parents and kindergarten teachers think about the topic? What do you consider important about the role of the material environment? The aim of my research was a kind of condition survey, during which my previous suggestion that parents want to give everything to their preschool children was confirmed. A XXI. century, it was proved that the concept of learning and the attitude associated with it were divided. According to the county of parents, the role of children’s learning on their own and for survival and the role of the material environment are decisive. It would be important to draw attention to the parental role model and sense of responsibility, to the scientific and relevant comprehensible information provided by professionals working in kindergarten